92:33=(32)2:33=34:33=34–3=3
52.252= 52.(52)2=52.54=52+4=56
a)92 : 33 = (32)2 : 33 = 34 : 33 = 3.
b) 52 . 252 = 52 . (52)2 = 52 . 54 = 56.
c) \(\left(\frac{1}{3}\right)^2\) . \(\left(\frac{1}{9.3}\right)^2\) = \(\frac{1^2}{3^2}\). \(\frac{1^2}{27^2}\)= \(\frac{1}{9}\).\(\frac{1}{729}\)= \(\frac{1}{2511}\)
a) \(9^2\div3^3=\left(3^2\right)^2\div3^3=3^4\div3^3=3\)
b) \(5^2\times25^2=5^2\times\left(5^2\right)^2=5^2\times5^4=5^6\)
c) \(\left(\frac{1}{3}\right)^2\times\left(\frac{1}{9\times3}\right)^2=\frac{1^2}{3^2}\times\frac{1^2}{27^2}=\frac{1}{9}\times\frac{1}{729}=\frac{1}{2511}\)
Cho xin cái li ke
a) \(9^2:3^3=\left(3^2\right)^2:3^3=3^4:3^3=3\)
b) \(5^2\cdot25^2=5^2\cdot\left(5^2\right)^2=5^2\cdot5^4=5^6\)
c) \(\left(\frac{1}{3}\right)^2\cdot\frac{1}{9}\cdot3^2\)
\(=\frac{1}{9}\cdot\frac{1}{9}\cdot9\)
\(=\frac{1}{9}\cdot1=\frac{1}{9}\)
a) \(9^2:3^3=\left(3^2\right)^2:3^3=3^4:3^3=3\)
b) \(5^2.25^2=5^2.\left(5^2\right)^2=5^2.5^4=5^6\)
c) \(\left(\frac{1}{3}\right)^2.\frac{1}{9}.3^2=\frac{1}{9}.\frac{1}{9}.9=\frac{1}{81}.9=\frac{1}{9}\)
_Chúc bạn học tốt_